PENDIDIKAN NASIONAL PERSPEKTIF PEMIKIRAN PENDIDIKAN ISLAM - Rosita Baiti (Fakultas Dakwah dan Komunikasi, Universitas Islam Negeri, Raden Fatah Palembang, 2013)
Education can not be separated from human life , society , and nation in order to ensure the survival and life . So the essence of education is a continuous process in accordance with the conditions , growth , and development of man himself . Many considered that the quality of education in Indonesia is far behind in education that exist in other countries , among which there are the drawbacks associated with the output of education at all levels of the character is weak , where the learning process that is likely to only strengthen intelligence . While other intelligence in the form of spiritual and emotional neglect , akibanya competence and competitiveness of education output to be weak , especially in relation to the global community association . Islamic education is an important part in developing the concept of national education , in an effort to strengthen the promotion of quality education that is capable of generating output character education that not only has the intellectual, but also spiritual and emotional intelligence , so that the state goal of building a complete Indonesian man can quickly be realized